Cardiovascular outcomes in patients with COPD-OSA overlap syndrome: A systematic review and meta-analysis. (June 2022) - Shah, Amar J.; Quek, Eleanor; Alqahtani, Jaber S.; Hurst, John R.; Mandal, Swapna
Summary: Chronic obstructive pulmonary disease (COPD) and obstructive sleep apnoea (OSA) are prevalent respiratory conditions that are independently associated with increased cardiovascular disease (CVD). It is not clear from current evidence whether COPD-OSA overlap syndrome confers an additive risk. This systematic review and meta-analysis investigated whether CVD was more prevalent in patients with overlap syndrome compared to either condition alone. We searched four electronic databases, screened 1826 records against the inclusion criteria. After screening, 18 retrospective, observational studies involving 4613 overlap patients, 16, 046 OSA patients and 1679 COPD patients met the inclusion criteria. A random-effects meta-analysis of five studies (I 2 = 61%) showed that overlap was associated with a significantly higher risk of hypertension compared to patients with COPD alone (OR = 1.68, 95%CI 1.21–2.35). Overlap was also associated with an increased risk of peripheral vascular disease compared to OSA alone (OR = 3.30 95%CI 2.66–4.10), with a subset of studies also suggesting an increased risk of ischaemic heart disease, heart failure, and cerebrovascular disease. However, it is worth noting that the findings are limited by the considerable heterogeneity of the studies, all of which were observational and retrospective in nature. This review highlights that patients with overlap syndrome have a high prevalence of CVD with some suggestion of an increased risk compared to patients with either condition alone.